Ultrasonic Studies of Dextrin in Aqueous Media at 298 K - Nithiyanantham, S.; Palaniappan, L. (Asian Journal of Chemistry, 2010)
The ultrasonic velocity, density and viscosity of dextrin in aqueous medium were measured at 298 K. The acoustical parameters such as adiabatic compressibility, free length, free volume, internal pressure, acoustical impedance, relative association, Rao's constant and Wada's constant are calculated. The results are interpreted in terms of molecular interaction between the components of the mixtures.